THE RAPID GROWTH OF THE LIBYAN OIL INDUSTRY - رؤف مصطفى, محمد (Dirasat in Economics and Business, 1966)
Introduction It is noted that oil exploration in Libya started less than ten years ago. The first important find was only six years ago, and the first shipment was made three and a half years ago. During 1964, however, Libya's oil exports had risen to 314 million barrels, or more than forty million tons. Expansion is virtually certain to continue for several years more, though the pace may not be so vast as in the last year or two. The increases in output from the ten established fields only awaited completion of further pipeline and of improved shipping facilities. Exports, have already reached nearly 1.3 million barrels per day. Further expansion may come from an eleventh oilfield discovered by British Petroleum in an even more remote and difficult part of the country, five hundred miles out of Tobruk. Factors Promoting Rapid Growth. Libya's rapid rise as a petroleum power has been largely due to its oil legoslation. The 1953 Minerals Law, the 1955 Comprehensive Petroleum Law, Number 25, and subsequent amendments all were aimed at encouraging rapid evaluation and development. Competition has been fostered by the granting of a large number of concessions to many firms. Unlike early concession deals in Saudi Arabia. Iran and Iraq, where essentially one company or a consortium held a concession monopoly, Libya now has agreements with nineteen firms involving 87 separate concessions. 80 This is a survey of the important characteristics of the new regulation being applied this year in the Faculty of Commerce and Economics. We cannot prophesy the efficiency of this amendment, except after its application for a sufficient time, so that the weaknesses may be known and further modification be envisaged. Summing up, we believe that the points raised will help prepare a graduate who can contribute more effectively to the economic development envisaged by the different governmental departments. The rapid evolution of this country shall bring in its train a flourishing economy for which we must prepare future generations. The Faculty of Commerce and Economics as an educational institution takes part, together with the other Faculties of this University and the different educational institutes, in the preparation for this development.